TAKHRIJ AL-HADITS TENTANG PERALATAN MAKAN NABI SAW - Hudaya, Hairul (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2016)
For the Muslims, the position of the Prophet Muhammad is not only transmitting the revelations, but also explaining and realizing them in all aspects of his life. Therefore, the description of how and what he ate is included as parts of the hadith. Nevertheless, the practice of hadith can not be separated from the assessment of the quality of these hadith. The results showed that the hadith associated with the Prophet?s tableware and Food is authentic both from its sanad and matan. The Hadith can be understood as a form of the humble life style of the prophet.  This attitude fits with what is said in the Qur'an and the Hadiths.